Chymase Inhibitor as a Novel Therapeutic Agent for Non-alcoholic Steatohepatitis - Takai, Shinji; Jin, Denan (Frontiers in Pharmacology, 2018)
Non-alcoholic steatohepatitis is characterized by inflammation and fibrosis, in addition to steatosis, of the liver, but no therapeutic agents have yet been established. The mast cell protease chymase can generate angiotensin II, matrix metalloproteinase-9 and transforming growth factor-β, all of which are associated with liver inflammation or fibrosis. In animal models of non-alcoholic steatohepatitis, augmented chymase has been observed in the liver. In histological analysis, chymase inhibitor prevented hepatic steatosis, inflammation and fibrosis. Chymase inhibitor also attenuated the augmentation of angiotensin II, matrix metalloproteinase-9 and transforming growth factor-β observed in the liver of non-alcoholic steatohepatitis. Oxidative stress, inflammatory markers, and collagen were attenuated by chymase inhibition. Moreover, chymase inhibitor showed a mitigating effect on established non-alcoholic steatohepatitis, and survival rates were significantly increased by treatment with chymase inhibitor. In this review, we propose that chymase inhibitor has potential as a novel therapy for NASH.